2013
DOI: 10.1017/sjp.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

Meaningfulness in Work in Brazilian and French Creative Industries

Abstract: This study aimed to investigate the meaningfulness that Brazilian and French artists find in their work, considering the historic French cultural influence in the Brazilian creative industry. The specific objective was to cross-culturally validate a model of meaningfulness in work that was developed in French Canada and that includes five latent variables: learning and development, utility of work, quality of working relationships, autonomy, and moral correctness. The present study used a French Canadian measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Entrepreneurial aspiration has important implications for work outcomes and affects the implementation process of the psychological employment contract (Ballout, 2007). Understanding creative entrepreneurs' sense of meaning in their work can reveal their expectations of it and the values they place on it (Bendassolli and Borges-Andrade, 2013).…”
Section: Entrepreneurial Satisfaction and Aspiration Of Creative Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurial aspiration has important implications for work outcomes and affects the implementation process of the psychological employment contract (Ballout, 2007). Understanding creative entrepreneurs' sense of meaning in their work can reveal their expectations of it and the values they place on it (Bendassolli and Borges-Andrade, 2013).…”
Section: Entrepreneurial Satisfaction and Aspiration Of Creative Entrepreneursmentioning
confidence: 99%
“…Social recognition means receiving status from those in communities who acknowledge a person's contribution (Kasser et al, 1996). Meaning of work, a psychological mechanism, is involved in the perception or production of meaning in relation to work (Bendassolli and Borges-Andrade, 2013). As such, recognizing and acting upon opportunities are important parts of entrepreneurship, and the ultimate goal of entrepreneurial activity involves entrepreneurial satisfaction and aspiration.…”
Section: Entrepreneurial Alertness Entrepreneurial Satisfaction and A...mentioning
confidence: 99%
“…One reason may be related to the sample composition. It is possible, for example, that the participants in the current sample might be closer, in terms of working values and representations, to a work culture associated much more with traditional economic activities than to a creative culture -something that has already been suggested by other studies with artists (e.g., Bendassolli & Borges-Andrade, 2013;Menger, 2002Menger, , 2009. The valorization of expressiveness as a single factor may be related to the socialization in artistic culture, which has been pointed out to be a culture marked by particular orientations regarding work, occupation, work-life balance, and preferences (e.g., Chateau, 2008;Menger, 1999Menger, , 2009.…”
mentioning
confidence: 75%
“…Sense and meaningful or meaningfulness may have the same translation into Portuguese. In English, there are theoretical differences between these words, but analysis of the differences lies beyond the scope of this paper (for this, see Bendassolli & Borges-Andrade, 2013). 1 Conceptual imprecisions are related to problems in our ways of understanding what concepts are and what their role is in scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…of study concerning the sense/meaning of work, as suggested by Borges (1998) and Tolfo et al (2011), among others (e.g., Bendassolli & Borges-Andrade, 2013;Bendassolli & Gondim, 2014). Operationally, we first characterize the sense/meaning research productions, identifying authorship, year, and geographical place of publication in addition to methodological aspects of the studies.…”
mentioning
confidence: 99%